Photoeletrocatalytic activity of a Cu 2O-loaded self-organized highly oriented TiO 2 nanotube array electrode for 4-chlorophenol degradation - Hou, Y.; Li, Xin Yong; Zou, X.; Quan, X.; Chen, G. (American Chemical Society, 2009)
Differently sized Cu 2O nanoparticles have been assembled photocatalytically on the surface of self-organized highly oriented TiO 2 nanotubes obtained by anodization of a Ti sheet in fluoride- containing electrolytes. X-ray diffraction analysis identifies an anatase structure and fine preferential orientation of (101) planes. The UV-vis absorption edge of the TiO 2 nanotube arrays shift to lower energy after Cu 2O loading. The composite array electrode exhibits a higher photovoltage response than the TiO 2 powders directly deposited on a Ti sheet. The highest photoconversion efficiencies observed for the Cu 2O-loaded electrode are 17.2% and 0.82% under UV light and visible light irradiation, respectively. Especially, the composite array electrode shows a higher efficiency than the nonloaded one for the photoelectrocatalytic decomposition of 4-chlorophenol. The improved photoeletrocatalytic activity of the TiO 2/Cu 2O composite array electrode is attributed to the synergistic effect of Cu 2O nanoparticles and TiO 2 nanotube arrays. The Cu 2O nanoparticles could enhance the efficiency of photon harvesting and reduce the chances of electron-hole recombination by sending the electrons to the conduction band of TiO 2 nanotubes. The accumulated electrons in the conduction band of TiO 2 nanotubes would reduce oxygen to form peroxides for enhanced advanced oxidation. The byproducts were identified by high- performance liquid chromatography. © 2009 American Chemical Society.